Development and Validation of UV-Visible Spectrophotometric Method for the Determination of 5-Hydroxymethyl Furfural Content in Canned Malt Drinks and Fruit Juices in Ghana - Joseph K. Adu; Cedric D. K. Amengor; Emmanuel Orman; Nurudeen Mohammed Ibrahim; Maryjane O. Ifunanya; Dylan F. Arthur (Journal of Food Quality)
A simple, rapid, accurate, and less expensive spectrophotometric method has been developed for the quantitation of 5-hydroxymethyl furfural (5-HMF) levels in canned malt drinks and fruit juice drinks sampled in the Kumasi Metropolis, Ghana. The quantitation is based on the selective maximum absorption of ultraviolet radiation by 5-HMF at the wavelength (λmax) of 284 nm using acetonitrile : water (50 : 50 v/v) as the solvent system. The method was established to be specific, precise, and accurate over a concentration range of 0.001 mg/ml–0.02 mg/ml. 5-HMF levels in fruit juice samples (A1–A10) were between 0.132 mg/ml and 0.438 mg/ml, and these levels were shown to be comparable (t = 2.200;p=0.0553) to the contents in the canned malt samples (M1–M10) which were between 0.3140 mg/ml and 0.7170 mg/ml. The study failed to show any dependence of 5-HMF levels on the composition of the product as well as the manufacturing process adopted. The length of storage did also not significantly affect the 5-HMF levels in the products.